Kendala Bahasa pada BIPA Anak Diaspora di Mindanao dalam Perspektif Neuropsikolinguistik - Yunia Tiara Riski; Wahyu Sukartiningsih; Hendratno; Mochamad Nursalim; Suryanti; Diana Rahmasari; Muhammad Nur Huda (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to analyze the language barriers experienced by Indonesian diaspora children in Mindanao in learning Indonesian for Foreign Speakers (BIPA) from a neuropsycholinguistic perspective by identifying the forms of decline in Indonesian language competence and the neurocognitive factors influenced by a multilingual environment. The study employed a qualitative approach using a Research and Development (R&D) design based on the 4D model, with a particular focus on the define stage. The research subjects consisted of seven students and two teachers at the Indonesian School of Davao, selected through purposive sampling. Data were collected through semi-structured interviews, participant observation, and document analysis and were analyzed using an interactive model involving data reduction, data presentation, and conclusion drawing. The findings indicate that the language barriers experienced by the participants included difficulties in syntactic structure, tense usage, language registers, and code-mixing caused by interference from Visayan and Tagalog. Contrastive analysis revealed that differences in sentence patterns (S-V-O vs. V-S-O) and grammatical systems were the primary sources of errors. From a neuropsycholinguistic perspective, these barriers were associated with limitations in working memory, attention, and lexical representation, which were influenced by limited exposure to the Indonesian language. The findings also showed that the students’ receptive and expressive language abilities remained limited, particularly in command comprehension, vocabulary mastery, and verbal memory. This study contributes theoretically to the enrichment of neuropsycholinguistic studies in the context of diaspora children and language learning. Practically, the findings provide a foundation for designing BIPA instruction that is adaptive, contextual, and aligned with learners’ neurocognitive characteristics.